Success stories of implementation of antimicrobial stewardship: a narrative review. (14th November 2014) - Huttner, B.; Harbarth, S.; Nathwani, D.; the ESCMID Study Group for Antibiotic Policies (ESGAP)
Abstract It has been increasingly recognized that antimicrobial stewardship (AMS) has to be a key component of any efforts that aim to mitigate the current global antimicrobial resistance (AMR) crisis. It has also become evident that AMR is a problem that cannot be tackled by single institutions or physicians, but needs concerted actions at regional, national and supra‐national levels. However, it is easy to become discouraged, given the problems that are often encountered when implementing AMS. The aim of this review is to highlight some of the success stories of AMS strategies, and to describe the actions that have been taken, the outcomes that have been obtained, and the obstacles that have been met. Although the best approach to effective AMS remains elusive and may vary significantly among settings, these diverse examples from a range of healthcare contexts demonstrate that effective AMS is possible. Such examples will inform others and encourage them to formally evaluate and share their results with the global stewardship community.